Sinalização de anexina A1: papel das vias de EGFR E IL-6 nos cânceres de próstata e mama - Mota, Sara Teixeira Soares (2021)
Anexin A1 (anxa1) is a 37 kDa protein that binds to calcium-dependent membrane phospholipids, being responsible for regulating inflammation, the organization of cell membranes and vesicular trafficking. Anxa1 is expressly expressed in cytoplasm, where it presents an anti-inflammatory activity. In the nucleus is involved in regulating transcription and therefore gene functioning. Anxa1 can also be cleaved proteelically generating a 33-kDa fragment and releasing its N-terminal cleaved peptide, which is biologically active. Both the peptide and the total length protein can be secreted to the extracellular medium, where they are able to activate formylated peptide receptors (FPRS), thus triggering an autocrine signaling. The autocrine signaling axis anxa1 / fpr1 is involved in pro-invasive and pro-tumor properties, mainly from tumors in more advanced stages, such as negative triple breast cancer (CMTN) and castration resistant prostate cancer (CRPC). Anxa1 plays relevant roles in malignant transformation, activating oncogenes and inactivating tumor suppressor genes, inducing cellular proliferation and invasion and formation of metastases. Therefore, investigate the signaling of ANXA1, as well as interaction with other molecules in the various types of tumors, is essential to elucidate the particularities of this protein and thus develop new diagnostic and therapeutic strategies for different malignant neoplasms. In tumors, ANXA1 performs pro-inflammatory activity, inducing a favorable tumor microenvironment (TME) with the promotion of growth and circulation of malignant cells. Therefore, in Chapter I, we reviewed the role of ANXA1 at the establishment of the tumor microenvironment, focusing on immunosuppressive and immunomodulating activities. First, we describe how cancer cells suppress the activities of the immune system, favoring the malignancy and the spread of cancer. Next, we present the main characteristics of the TME and that the presence of some immunological cells in its composition creates a highly immunosuppressive environment, which favors the growth and progression of the tumor. We portray the structure and characteristics of ANXA1 as well as their roles in malignant transformation. Finally, we evidenced as ANXA1 promotes tumor suppression by interaction with the receptor of the epidermal growth factor (EGFR), triggering an immune exhaust mechanism by cancer cells. In the second chapter, we show that ANXA1 activates autocrine signaling in CRPC cells through FPR1. In addition, in the CRPC, we observed that the autocrine signaling of ANXA1 promotes nuclear location in EGFR. It has already been previously described that, once in the nucleus, EGFR is associated with progression of prostate cancer for castration resistant phenotype. When inhibited the FPR1 using Cyclsoporin H, the nuclear location of the EGFR and its downstream signage in the CRPC strains were blocked. We suggest, then, that inhibition of the autocrine signaling of ANXA1 and, consequently, of the nuclear location of EGFR can be a relevant strategy for the treatment of CRPC In the last chapter, we demonstrate an interaction between the signage routes of ANXA1 / FPR1 and Interleukin-6 (IL-6) and Stat3 (transcription factor activated by tyrosine kinases 3) in the CMTN. Our results showed that in CMTN, MDA-MB-231 and MDA-MB-157 lineages, IL-6 signaling cascade modulates the autocrine axis activation anxa1 / fpr1. When treating sexic female mice transplanted with MDA-MB-231 cells with Tocilizumab, a humanized monoclonal antibody that operates by blocking IL-6 receptors, we observed the reduction of tumor growth and inhibition of metastases formation. Finally, we show that IL-6 / STAT3 and ANXA1 / FPR1 pathways influence TME, altering the motility of fibroblasts. We suggest that the inhibition of IL-6 can be used as a possible therapeutic intervention and / or a new adjuvant therapy to improve the clinical outcome of patients with CMTN by blocking the autocrine signaling of ANXA1, slowing tumor progression.Finally, we demonstrate that AnxA1 stimulates a favorable tumor microenvironment which leads to immune escape by cancer cells. And in more aggressive prostate tumors such as CRPC, the autocrine signaling pathway of AnxA1 and FPR1 promotes the nuclear localization of EGFR, and that this localization plays an important role in cell survival and aggressiveness of CRPC cells. In triple negative breast tumors, the IL-6 pathway was shown to be a compensatory mechanism for signaling the AnxA1 and FPR1 axis, and these pathways, in addition to playing an important role in the aggressiveness of the CMTN, also influence the TME, reducing the motility of fibroblasts. Therefore, this work effectively contributed to the scientific community demonstrating that Annexin A1 plays different roles in tumor progression and that further studies on this molecule, and especially on the AnxA1/FPR1 autocrine signaling pathway, are relevant for a greater understanding of the most aggressive tumors, as well as possible therapeutic strategies.